بوابة الحجز الإلكتروني للفعاليات - - حسان زبيدي - علي الأخوص - سيف الدين كرمادي (university of eloued جامعة الوادي, 2024)
يستعرض العمل تأثير الإشعاع الشمسي على نمو المحاصيل الزراعية وإنتاجيتها. يشمل ذلك تحليل أنماط البناء الضوئي في نباتات C3 وC4، حيث يُظهر أن نباتات C4 أكثر كفاءة في إنتاجية الكتلة الحيوية. يعد اعتراض الإشعاع الشمسي من العوامل الحاسمة في نمو المحاصيل، إذ يؤثر في العمليات الفسيولوجية مثل التمثيل الضوئي والنتح. تتناول الدراسة تأثير زاوية الأوراق، وخصائص سطحها، وترتيبها على اعتراض الضوء، وأهمية الإشعاع النشط ضوئيا (PAR) في هذه العملية. يُقدر مؤشر مساحة الورقة (LAI) كمعيار لقدرة النبات على امتصاص الضوء، مما يؤثر على إنتاجية المحاصيل. تركز الاستراتيجيات الزراعية على تعظيم اعتراض الإشعاع الشمسي من خلال ممارسات مثل التسميد والري. كما تطرق العمل لتأثير نقص الماء والنيتروجين على كفاءة التمثيل الضوئي، وتقييم طرق قياس الإشعاع المعترض، بما في ذلك استخدام التقنيات الحديثة مثل الاستشعار عن بعد والصور الفوتوغرافية الرقمية The work reviews the effect of solar radiation on the growth and productivity of agricultural crops. This includes analyzing photosynthesis patterns in C3 and C4 plants, showing that C4 plants are more efficient at biomass productivity. Interception of solar radiation is a critical factor in crop growth, affecting physiological processes such as photosynthesis and transpiration. The study examines the effect of leaf angle, surface characteristics, and arrangement on light interception, and the importance of photoactive radiation (PAR). In the process. The leaf area index (LAI) is estimated as a benchmark for a plant's ability to absorb light, affecting crop productivity. Agricultural strategies focus on maximizing solar radiation interception through practices such as fertilization and irrigation. The work also addressed the impact of water and nitrogen shortages on photosynthesis efficiency, and evaluated methods for measuring intercepted radiation, including the use of modern technologies such as remote sensing and digital photographs.
مدكرة ليسانس اعلام الي
Keywords: تأثير الإشعاع الشمسي - المحاصيل الزراعية – التمثيل الضوئي; influence of solar radiation - agricultural crops – photosynthesis